2021
DOI: 10.3390/ijerph182111670
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Influencing the Emission of Ultrafine Particles during 3D Printing

Abstract: This paper presents a complex and extensive experimental evaluation of fine particle emissions released by an FDM 3D printer for four of the most common printing materials (ABS, PLA, PET-G, and TPU). These thermoplastic filaments were examined at three printing temperatures within their recommended range. In addition, these measurements were extended using various types of printing nozzles, which influenced the emissions considerably. This research is based on more than a hundred individual measurements for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Chýlek i wsp. [24] wskazali natomiast, że parametry konstrukcyjne drukarki, takie jak średnica dyszy, nie mogą być pomijane jako czynnik wpływający na emisję cząstek podczas druku 3D. Ponadto szybkie zmiany termodynamiczne, w tym bardzo szybki wzrost temperatury i ciśnienia, mogą prowadzić do zmian w składzie substancji chemicznych powstających w procesie [23].…”
Section: Parametry Wpływające Na Poziom Emisji Substancji Chemicznych...unclassified
“…Chýlek i wsp. [24] wskazali natomiast, że parametry konstrukcyjne drukarki, takie jak średnica dyszy, nie mogą być pomijane jako czynnik wpływający na emisję cząstek podczas druku 3D. Ponadto szybkie zmiany termodynamiczne, w tym bardzo szybki wzrost temperatury i ciśnienia, mogą prowadzić do zmian w składzie substancji chemicznych powstających w procesie [23].…”
Section: Parametry Wpływające Na Poziom Emisji Substancji Chemicznych...unclassified
“…Industrial processing of thermoplastics at temperatures of 180–280 °C, where printing is mainly done, leads to undesirable emissions of volatile and semi-volatile organic compounds and particles. The most critical period seems to be the beginning of the printing process, when the particles emitted are usually at their highest concentration and smallest size [ 93 ]. Reducing the nozzle temperature, selecting a material that operates at a lower nozzle temperature and using lower-emission filaments (e.g., PLA filaments, which have low ultrafine particles (UFP) [ 94 ]) can reduce emissions of volatile organic compounds and ultrafine particles [ 95 ].…”
Section: Concerns and Challengesmentioning
confidence: 99%
“…In many previous studies, experiments were carried out in experimental chambers to analyze the properties and concentrations of ultrafine and fine particles emitted from 3D printers, and the results confirmed that the 3D printers emit large amounts of ultrafine and fine particles. [17][18][19][20] Weber et al 4 measured the ultrafine and fine particle emissions from the use of the most commonly used filament materials in FDM-3D printers, such as acrylonitrile-butadiene-styrene (ABS) and polylactic acid (PLA), through an experiment in the experimental chamber and reported that the particle size ranges from 11.5 to 11.6 nm, and ABS shows an emission rate 10 times higher than that of PLA. This result can be understood in that, due to its high melting temperature, ABS emits more particles than PLA.…”
Section: Ultrafine and Fine Particles Emitted From 3d Printingmentioning
confidence: 99%